Epidemiology of congenital dysplasia or dislocation of the hip (CDH) in newborns, Babol, 1996-97 - N Jan Mohammadi (Babol University of Medical Sciences, 2001)
Objective: Developmental dysplasia or dislocation of the hip (DDH) is a common and serious problem of newborns and infants. In different parts of the world, the incidence of DDH is different according to their geographical area, race, tribe and culture. With regard to epidemiological characteristics and risk factors, by early diagnosis and treatment can reach a pleasing conclusion and make it possible to reduce individual and social problems. Methods: With simple sequential sampling method, 3498 newborns in two governmental and private maternity were examined by Ortolani and Barlow tests for diagnosing DDH. Also, all suspicious and affected cases were evaluated by sonography. Findings: Suspicious and unstable cases and dislocation of the hip were 6.4%, 7%, 5% respectively. Females were affected 3 times more than males newborns who were born by abdominal delivery were affected 4.7 times more than ones who were born by vaginal delivery (P<0.001). Newborns of first delivery were affected more than subsequent ones. For diagnosis of DDH, Barlow test was more specific and Ortolani test was more sensitive. Sonography confirmed all cases. Newborns with breech condition were not affected by DDH. Right hip was affected 3.2 times more than left hip. All suspicious immature newborns after complete evaluation were affected by DDH and immature newborns were affected more than mature ones by DDH. Conclusion: Dysplasia of the hip with some characteristics such as affected hip, prevalence in immature infants connected with breech and cesarean conditions. Barlow test was more specific in diagnosis of DDH in comparison to Ortolani test and sonography examination was known as a certain method for paraclinical diagnosis.